Development of PBL-Based Interactive Physics E-Books to Improve Students' Critical Thinking Abilities and Digital Literacy - Hutauruk, Novri Elisabeth; Rosana, Dadan (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This research is development research using the ADDIE model with the stages of analyze, design, develop, implementation and evaluation. The research design used is Quasi Experimental Design. This research was conducted at SMA N 1 Ngaglik Sleman, Yogyakarta. This research aims to: (1) produce interactive physics e-book media based on problem based learning that is suitable for use in high school physics learning; (2) determine the practicality of using interactive physics e-book media based on problem based learning in improving students' critical thinking skills and digital literacy on temperature and heat material; (3) determine the effectiveness of using interactive physics e-book media based on problem based learning in improving students' critical thinking skills and digital literacy on temperature and heat material; and (4) describe the results of measuring students' critical thinking abilities and digital literacy. The data analysis technique uses Quest for empirical testing of the question instrument, N-gain, and effect size testing using GLM. The research results show that the interactive physics e-book media based on problem-based learning that was developed is feasible, practical, able to improve critical thinking skills and digital literacy. This al is based on N-gain and is supported by the GLM results in the effect size test which shows that students' critical thinking skills and digital literacy are in the strong category.